2013
DOI: 10.1590/s0102-311x2013000800015
|View full text |Cite
|
Sign up to set email alerts
|

Metodologia e perfil sociodemográfico, cognitivo e de fragilidade de idosos comunitários de sete cidades brasileiras: Estudo FIBRA

Abstract: A study was designed to identify conditions of frailty in relation to social, demographic, health, cognitive, functional, and psychosocial variables in community-dwelling elderly. The article presents the methodology and preliminary data. A total of 3,478 elderly (65 years and older) were selected from probabilistic samples of seven Brazilian cities chosen by convenience and participated in a data collection session in a community setting. The following characteristics predominated: women (67.7%), married (48%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
102
3
89

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(208 citation statements)
references
References 0 publications
14
102
3
89
Order By: Relevance
“…Women more often expressed a low level of satisfaction with their memory than men, confirming earlier data 18 indicating that women have a lower sense of self-efficacy for memory and cognition than men, and that their cognitive performance is indeed worse due to gender stereotypes and a lack of career opportunities.…”
Section: P-valuesupporting
confidence: 83%
See 1 more Smart Citation
“…Women more often expressed a low level of satisfaction with their memory than men, confirming earlier data 18 indicating that women have a lower sense of self-efficacy for memory and cognition than men, and that their cognitive performance is indeed worse due to gender stereotypes and a lack of career opportunities.…”
Section: P-valuesupporting
confidence: 83%
“…In each location, a simple random sampling of urban census sectors was conducted using a quantity that corresponded to the ratio between the number of elderly individuals expected and the urban census tracts. 18 The present study used data from the cities of Belém-PA and Campinas-SP, both of which had a population in excess of one million at the time of the recruitment and data collection. Belém had a gross domestic product (GDP) of R$ 9793.00 per capita and Campinas had a GDP of R$ 29,731.00 per capita.…”
Section: Methodsmentioning
confidence: 99%
“…In Brazil, the prevalence in six states was 25% in 2008 and 2009 6 , higher than that observed in other countries in Latin America and the Caribbean, such as Argentina (8.3%) and Barbados (21.3%) 7 .…”
Section: Introductionmentioning
confidence: 69%
“…A study of seven Brazilian cities with a sample of 3,478 elderly found that 51.9% of the elderly were considered pre-frail, 39.1% were non frail and 9% frail (20) .…”
Section: Discussionmentioning
confidence: 99%